SOX3 duplication: A genetic cause to investigate in fetuses with neural tube defects. (9th August 2019) - Hureaux, Marguerite; Ben Miled, Selima; Chatron, Nicolas; Coussement, Aurelie; Bessières, Bettina; Egloff, Matthieu; Mechler, Charlotte; Stirnemann, Julien; Tsatsaris, Vassilis; Barcia, Giulia; Turleau, Catherine; Ville, Yves; et al.
Abstract: Objective: Neural tube defects (NTDs) are one of the most common congenital anomalies caused by a complex interaction of many genetic and environmental factors. In about 10% of cases, NTDs are associated with genetic syndromes or chromosomal anomalies. Among these, SOX3 duplication has been reported in some isolated cases. The phenotype associated with this microduplication is variable and includes myelomeningocele (MMC) in both sexes as well as hypopituitarism and cognitive impairment in males. In order to determine the prevalence of this anomaly in fetuses with MMC, a retrospective cohort of fetuses with MMC was analyzed by quantitative PCR (qPCR) targeting SOX3 locus. Methods: The detection of an SOX3 microduplication by chromosomal microarray analysis (CMA) in two female fetuses with MMC prompted us to analyze retrospectively by qPCR this gene in a cohort of 53 fetuses with MMC. Results: In addition to our two initial cases, one fetus harboring an Xq27.1q28 duplication that encompasses the SOX3 gene was detected. Conclusion: Our data demonstrate that SOX3 duplication is a genomic imbalance involved in the pathogenesis of NTDs. In addition, our survey highlights the importance of CMA testing in fetuses with NTDs to enable genetic counseling upstream of any considerations of in utero fetal surgery. Abstract : What is already known about this topic? In males, SOX3 genetic alterations are associated with X‐linked hypopituitarism and cognitive impairment. More recently, Xq27.1 microduplications involving SOX3 gene have been reported in some isolated cases of MMC in both sexes. What does this study add? SOX3 microduplication is a genomic imbalance reported in a number of fetuses with MMC. Our survey highlights the importance of investigating this anomaly using a broad genomic scan such as CMA that will detect SOX3 duplication and other CNVs in fetuses with NTDs for genetic counseling.